Evaluation of the Lesions Mimicking Anal Penetration Two Case Report - Demirçin, Sema; Karagöz, Y. Mustafa; Sargın, Osman Özgür; Atılgan, Mehmet (The Bulletin of Legal Medicine, 2007)
Small area of ecchymosis at anal mocosa and skin-mucosa junction and ecchymosis surrounding anus like a ring or seal are important findings of acute actual anal penetration. Physical examination of anal penetration cases may not always reveal the classical findings of sexual abuse. In addition to this the differantial diagnosis of previously present lesions at perianal region, must be also done. Sometimes various lesions may mimic anal penetration findings. In this case report, two and four years old two cases who had been consultated by Forensic Medicine Department with prediagnosis of anal penetration while they were being followed up in the Intensive Care Unit after being admitted to our hospital with near drowning has been discussed. The premortem physical examination of the two cases revealed suspicious findings of actual anal penetration however the postmortem examination and autopsy lacked these findings. Findings similar to that of anal penetration may be present in the absence of actual anal penetration therefore serious forensic mistakes may result from evaluation of these patients by inexperienced medical practitioner for this reason be consider that the evaluation of these patients by reference centers will be more convenient.Key words: Anal penetration, anal intercouse, autopsy, anal findings.
Keywords: anal penetration; anal intercourse; autopsy; anal findings